Changing Consumer Behaviour and Soft Drinks Marketing in North-Goa, A Case Study - Kumar, D.N.S. (Indian Journal of Marketing, 2008)
Consumer behaviour has an important bearing on the sales of a product. Behavioral patterns change depending upon a number of variables, such as, mindset of a consumer, climate, level of income, taste, expectations and environment in which he makes his decisions. In a Global context of market-oriented economies, consumer has become the king. He operates through his sovereign power. He enjoys lot of freedom in designing his decisions. Markets have no longer remained "sellers markets". They have obviously turned in "Buyers Markets". Soft drink industry is one of the biggest industries on the Industrial horizon of Goa. Its support to tourism industry, liquor industry and hotel industry is un-imaginable and non-measurable. It also meets to a major extent the grave unemployment problem in the area. In the case of consumer convenience product soft drink, marketer witness a often change in the consumer behaviour as the product unit price is low, substitute brands are many, closely located and easily accessible dealers, and most cases different roles of purchase unit are performed by a single individual. From the study it is noticed that, the behaviour of consumers consuming soft drinks shows changes due to climatic variation and consumer behaviour doesn’t show a marked changes with a change in price of a product.